Surface functionalized dry ion conductor and preparation method and application thereof
By coating the surface of the dry ion conductor with double bonds and RAFT reagent, surface functionalized dry ion conductors with high hydrophobicity and self-healing properties is prepared, which solves the problem of performance instability caused by hygroscopy of dry ion conductors and is suitable for flexible wearable devices.
Patent Information
- Application Number
- CN202411990948.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
Existing dry ion conductors are prone to moisture absorption when working in the air for a long time, resulting in interference in mechanical properties and conductive stability, which cannot meet the needs of flexible wearable devices.
By coating the surface of the dry ion conductor with double bond-containing hydrophobic monomer and RAFT reagent, and curing with ultraviolet light irradiation, surface functionalized dry ion conductors with high hydrophobicity and self-healing properties were prepared.
It realizes the self-healing and high hydrophobic properties of dry ion conductors, alleviates the instability of mechanical and electrical conductivity caused by hygroscopy, is suitable for large-scale production and has high commercial and social practical value.
Smart Images

Figure CN119763890A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of dry ion conductor materials, and in particular to a surface functionalized dry ion conductor and a preparation method and application thereof. Background Art
[0002] At present, most of the existing conductive materials based on metal powder, conductive carbon black, polypyrrole, polyaniline, graphene, etc. have many disadvantages, such as easy oxidation of metals and unstable conductive properties; the addition of hard materials leads to mismatch of Young's modulus and easy fall-off of fillers; carbon-based materials have high cost, complex process and poor optical properties. Dry ion conductors have attracted much attention due to their advantages such as low raw material price, green and pollution-free, high molecular utilization rate and strong processability. However, the hydrogen bond donors in the current polymerizable low eutectic solvents are often acrylic acid, and the hydrogen bond acceptors are often solid quaternary ammonium salts, but both are highly hygroscopic, resulting in the dry ion conductors prepared by this type of PDES absorbing moisture when working in the air for a long time, which will seriously interfere with the mechanical properties and conductive stability of the dry ion conductors. With the growing demand for flexible wearable devices, it is urgent to solve the moisture absorption problem of dry ion conductors working for a long time. Summary of the invention
[0003] Based on this, the present invention aims to overcome at least one defect of the prior art and provide a surface functionalized dry ion conductor and a preparation method thereof. The surface functionalized dry ion conductor has the excellent mechanical and electrical properties of a dry ion conductor and also has self-healing properties and surface hydrophobic properties. The preparation method of the surface functionalized dry ion conductor is simple, suitable for large-scale production, and has extremely high commercial and social practical value.
[0004] The technical solution is as follows:
[0005] A method for preparing a surface functionalized dry ion conductor comprises the following steps:
[0006] S1, stirring and mixing the hydrogen bond donor, the hydrogen bond acceptor and the RAFT agent at 50-80° C. to obtain a polymerizable low eutectic solvent;
[0007] S2, irradiating the polymerizable low eutectic solvent under ultraviolet light to solidify it to obtain a dry ion conductor;
[0008] S3, blending a hydrophobic monomer containing a double bond with a RAFT agent, coating the mixture on the surface of the dry ion conductor, irradiating the mixture with ultraviolet light, and curing the mixture to obtain a surface functionalized dry ion conductor;
[0009] Wherein, in step S1, the hydrogen bond donor includes a soft monomer containing a C=C double bond and a hard monomer containing a C=C double bond; the hydrogen bond acceptor is a quaternary ammonium salt;
[0010] The molar ratio of the soft monomer, the hard monomer and the hydrogen bond acceptor is 1:(0.5-2):(0.2-1).
[0011] In one embodiment, the soft monomer is acrylic acid or citraconic acid; and / or the hard monomer is acrylamide or itaconic acid; and / or the quaternary ammonium salt is choline chloride or betaine monohydrate.
[0012] The present invention utilizes the characteristics of reversible addition-fragmentation chain transfer active polymerization without termination, transfer, and initiation rate greater than growth rate, and obtains low-dispersibility, topologically diverse and post-functionalized PDES dry ion conductors through simple and mild reactions, and then coats the surface with hydrophobic monomers and RAFT agents containing double bonds, and finally prepares dry ion conductors with high hydrophobicity on the surface. During the polymerization process, the RAFT agent directly absorbs light and becomes an excited state, and then the C=S double bond is cleaved to generate active initiation / propagation free radicals and thiocarbonyl sulfide to form initiation sites, and soft monomers and hard monomers containing C=C double bonds as hydrogen bond donors are polymerized as polymerizable monomers, and can form molecular chains under the initiation of the active sites. At the same time, hydrogen bond donors and hydrogen bond acceptors can form a low eutectic solvent, and the dry ion conductor is cured by ultraviolet light irradiation, wherein the soft monomers and hard monomers containing C=C double bonds can provide relatively excellent mechanical properties, self-healing properties and optical properties through densely entangled polymer chains and synergistic hydrogen bond interactions. After the monomer reaction is completed, the RAFT agent combines with the polymer chain to form dormant species, which are well retained in the existing product and can be easily activated after being re-exposed to ultraviolet light. Therefore, it is a dry ion conductor that can be post-functionalized. Then, a hydrophobic monomer containing a double bond and a RAFT agent are coated on its surface, and the hydrophobic monomer is activated by a thiocarbonylthio reaction to extend the secondary chain, thereby preparing a dry ion conductor with a highly hydrophobic surface. This application uses RAFT active polymerization to guide PDES to prepare a dry ion conductor, which can obtain the mechanical properties, optical properties, and conductive properties possessed by other polymerization methods, while obtaining post-functionalization characteristics that other polymerization methods do not have, greatly enhancing the practical value of the dry ion conductor.
[0013] In one embodiment, the hydrophobic monomer containing a double bond is one or more of butyl acrylate (BA), 2,2,3,4,4,4-hexafluorobutyl acrylate (HA), and 2,2,3,3-tetrafluoropropyl methacrylate (TFPMA).
[0014] In one embodiment, the RAFT agent is ethyl 2-[(ethoxythiocarbonyl)thio]propionate.
[0015] In one embodiment, the molar ratio of the RAFT agent to the hydrogen bond donor in step S1 is 1:(100-600). More preferably, the molar ratio of the RAFT agent to the hydrogen bond donor in step S1 is 1:(300-400).
[0016] In one embodiment, the molar ratio of the RAFT agent to the hydrophobic monomer containing a double bond in step S3 is 1:(100-600). More preferably, the molar ratio of the RAFT agent to the hydrophobic monomer containing a double bond in step S3 is 1:(300-400).
[0017] In one embodiment, in step S1, the hydrogen bond donor, the hydrogen bond acceptor and the RAFT agent are stirred at 60 to 80° C. for 30 to 60 minutes to be uniformly mixed.
[0018] In one embodiment, the ultraviolet light irradiation time in step S2 and step S3 is 300 to 400 seconds.
[0019] The surface functionalized dry ion conductor prepared by the preparation method of the surface functionalized dry ion conductor is a dry ion conductor with a hydrophobic surface. Specifically, the contact angle of the surface functionalized dry ion conductor is 85 to 120°, more specifically 88 to 115°.
[0020] Furthermore, the surface functionalized dry ion conductor is a transparent material. More specifically, the visible light transmittance of the surface functionalized dry ion conductor is greater than 90%.
[0021] Furthermore, the surface functionalized dry ion conductor has self-healing properties.
[0022] Furthermore, the difference in conductivity of the surface functionalized dry ion conductor before and after functionalization is less than 28%.
[0023] Another object of the present invention is to provide an application of the surface functionalized dry ion conductor in the field of wearable electronics. The surface of the surface functionalized dry ion conductor has hydrophobicity, which can greatly alleviate the problem of unstable mechanical and conductive properties of the dry ion conductor when working for a long time, and the surface functionalized dry ion conductor has good light transmittance and flexibility.
[0024] The beneficial effects of the present invention are as follows: the present invention first prepares a polymerizable low eutectic solvent with a specific hydrogen bond donor, a hydrogen bond acceptor and a RAFT agent, and then cures the solvent under ultraviolet light to obtain a dry ion conductor. The dry ion conductor itself has excellent mechanical properties, electrical conductivity and self-healing properties. After the preparation of the dry ion conductor, the RAFT agent forms dormant species, which are well retained in the dry ion conductor. It is a surface-functionalized dry ion conductor. A hydrophobic monomer containing a double bond and a RAFT agent are then coated on its surface. The hydrophobic monomer is activated by a thiocarbonylthio reaction to extend the secondary chain, thereby preparing a dry ion conductor with a highly hydrophobic surface. The surface-functionalized dry ion conductor has the excellent mechanical and electrical properties of the dry ion conductor and also has self-healing and hydrophobic properties. The preparation method is simple, suitable for large-scale production, and has super high commercial and social practical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a digital photo of the transparent and functionalizable conductive elastomer of Example 3.
[0026] Figure 2 Digital photos of the hydrophobic properties of Example 3 before (a) and after (b) surface functionalization.
[0027] Figure 3 The electrical conductivity of (a) the elastomers of Examples 1 to 6 when the surface is not functionalized, and (b) the electrical conductivity of the elastomers after the surface is functionalized (coating with hydrophobic monomer butyl acrylate (BA)).
[0028] Figure 4 This is the contact angle of the dry ion conductor in Example 3 when no surface functionalization is performed.
[0029] Figure 5 This is the contact angle of the dry ion conductor after surface functionalization in Example 3.
[0030] Figure 6 : This is the contact angle of the dry ion conductor of Example 7 after surface functionalization (using hydrophobic monomer 2,2,3,3-tetrafluoropropyl methacrylate (TFPMA)).
[0031] Figure 7 : This is the contact angle of the dry ion conductor of Example 8 after surface functionalization (using hydrophobic monomer 2,2,3,4,4,4-hexafluorobutyl acrylate (HA)).
[0032] Figure 8 This is a diagram of the mechanical properties of the dry ion conductor after surface functionalization in Example 3.
[0033] Fig. 9 UV absorption spectra of the elastomer containing RAFT agent before and after photocuring. DETAILED DESCRIPTION
[0034] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention are further described in detail below.
[0035] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Example 1
[0036] A surface functionalized dry ion conductor, the preparation process is as follows:
[0037] S1: 7.21 g of acrylic acid as a hydrogen bond donor, 3.55 g of acrylamide, 6.98 g of choline chloride as a hydrogen bond acceptor, and 295.0 μL of RAFT agent ethyl 2-[(ethoxythiocarbonyl)thio]propionate were heated and stirred at 60° C. for 60 min to obtain a polymerizable deep eutectic solvent (PDES);
[0038] S2, irradiating the PDES under UV light (2 kW) for 300 s to obtain a dry ion conductor;
[0039] S3. 12.82 g of BA containing a double bond was mixed with 65.5 μL of ethyl 2-[(ethoxythiocarbonyl)thio]propionate, and then coated on the surface of the dry ion conductor. The mixture was irradiated with ultraviolet light for 300 to 400 s and cured to obtain a surface functionalized dry ion conductor. Example 2
[0040] A surface functionalized dry ion conductor, the preparation process is as follows:
[0041] S1. 7.21 g of acrylic acid as a hydrogen bond donor, 3.55 g of acrylamide, 6.98 g of choline chloride as a hydrogen bond acceptor, and 147.5 μL of ethyl 2-[(ethoxythiocarbonyl)thio]propionate were heated and stirred at 60° C. for 60 min to mix evenly to obtain a polymerizable deep eutectic solvent (PDES);
[0042] S2, irradiating the PDES under UV light (2 kW) for 300 s to obtain a dry ion conductor;
[0043] S3. 12.82 g of BA containing a double bond was mixed with 65.5 μL of ethyl 2-[(ethoxythiocarbonyl)thio]propionate, and then coated on the surface of the dry ion conductor. The mixture was irradiated with ultraviolet light for 300 to 400 s and cured to obtain a surface functionalized dry ion conductor. Example 3
[0044] A surface functionalized dry ion conductor, the preparation process is as follows:
[0045] S1. Mix 7.21 g of acrylic acid as a hydrogen bond donor, 3.55 g of acrylamide, 6.98 g of choline chloride as a hydrogen bond acceptor, and 98.5 μL of ethyl 2-[(ethoxythiocarbonyl)thio]propionate under heating and stirring at 60° C. for 60 min to obtain a polymerizable deep eutectic solvent (PDES);
[0046] S2, irradiating the PDES under UV light (2 kW) for 300 s to obtain a dry ion conductor;
[0047] S3. 12.82 g of BA containing a double bond was mixed with 65.5 μL of ethyl 2-[(ethoxythiocarbonyl)thio]propionate, and then coated on the surface of the dry ion conductor. The mixture was irradiated with ultraviolet light for 300 to 400 s and cured to obtain a surface functionalized dry ion conductor. Example 4
[0048] A surface functionalized dry ion conductor, the preparation process is as follows:
[0049] S1. Mix 7.21 g of acrylic acid as a hydrogen bond donor, 3.55 g of acrylamide, 6.98 g of choline chloride as a hydrogen bond acceptor, and 73.5 μL of ethyl 2-[(ethoxythiocarbonyl)thio]propionate under heating and stirring at 60° C. for 60 min to obtain a polymerizable deep eutectic solvent (PDES);
[0050] S2, irradiating the PDES under UV light (2 kW) for 300 s to obtain a dry ion conductor;
[0051] S3. 12.82 g of BA containing a double bond was mixed with 65.5 μL of ethyl 2-[(ethoxythiocarbonyl)thio]propionate, and then coated on the surface of the dry ion conductor. The mixture was irradiated with ultraviolet light for 300 to 400 s and cured to obtain a surface functionalized dry ion conductor. Example 5
[0052] A surface functionalized dry ion conductor, the preparation process is as follows:
[0053] S1. Mix 7.21 g of acrylic acid as a hydrogen bond donor, 3.55 g of acrylamide, 6.98 g of choline chloride as a hydrogen bond acceptor, and 59.0 μL of ethyl 2-[(ethoxythiocarbonyl)thio]propionate under heating and stirring at 60° C. for 60 min to obtain a polymerizable deep eutectic solvent (PDES);
[0054] S2, irradiating the PDES under UV light (2 kW) for 300 s to obtain a dry ion conductor;
[0055] S3. 12.82 g of BA containing a double bond was mixed with 65.5 μL of ethyl 2-[(ethoxythiocarbonyl)thio]propionate, and then coated on the surface of the dry ion conductor. The mixture was irradiated with ultraviolet light for 300 to 400 s and cured to obtain a surface functionalized dry ion conductor. Example 6
[0056] A surface functionalized dry ion conductor, the preparation process is as follows:
[0057] S1. Mix 7.21 g of acrylic acid as a hydrogen bond donor, 3.55 g of acrylamide, 6.98 g of choline chloride as a hydrogen bond acceptor, and 49.0 μL of ethyl 2-[(ethoxythiocarbonyl)thio]propionate under heating and stirring at 60° C. for 60 min to obtain a polymerizable deep eutectic solvent (PDES);
[0058] S2, irradiating the PDES under UV light (2 kW) for 300 s to obtain a dry ion conductor;
[0059] S3. 12.82 g of BA containing a double bond was mixed with 65.5 μL of ethyl 2-[(ethoxythiocarbonyl)thio]propionate, and then coated on the surface of the dry ion conductor. The mixture was irradiated with ultraviolet light for 300 to 400 s and cured to obtain a surface functionalized dry ion conductor. Example 7
[0060] A surface functionalized dry ion conductor, the preparation process is as follows:
[0061] S1. Mix 7.21 g of acrylic acid as a hydrogen bond donor, 3.55 g of acrylamide, 6.98 g of choline chloride as a hydrogen bond acceptor, and 98.5 μL of ethyl 2-[(ethoxythiocarbonyl)thio]propionate under heating and stirring at 60° C. for 60 min to obtain a polymerizable deep eutectic solvent (PDES);
[0062] S2, irradiating the PDES under UV light (2 kW) for 300 s to obtain a dry ion conductor;
[0063] S3. 20.01 g of TFPMA containing double bonds was mixed with 65.5 μL of ethyl 2-[(ethoxythiocarbonyl)thio]propionate, and then coated on the surface of the dry ion conductor. The mixture was irradiated with ultraviolet light for 300 to 400 s and cured to obtain a surface functionalized dry ion conductor. Example 8
[0064] A surface functionalized dry ion conductor, the preparation process is as follows:
[0065] S1. Mix 7.21 g of acrylic acid as a hydrogen bond donor, 3.55 g of acrylamide, 6.98 g of choline chloride as a hydrogen bond acceptor, and 98.5 μL of RAFT agent 2-[(ethoxythiocarbonyl)thio]butyl propionate under heating and stirring at 60° C. for 60 min to obtain a polymerizable deep eutectic solvent (PDES);
[0066] S2, irradiating the PDES under UV light (2 kW) for 300 s to obtain a dry ion conductor;
[0067] S3. 23.61 g of HA containing double bonds was mixed with 65.5 μL of ethyl 2-[(ethoxythiocarbonyl)thio]propionate, and then coated on the surface of the dry ion conductor. The mixture was irradiated with ultraviolet light for 300 to 400 s and cured to obtain a surface functionalized dry ion conductor. Example 9
[0068] A surface functionalized dry ion conductor, the preparation process is as follows:
[0069] S1. A hydrogen bond donor 13.01 g of citraconic acid, 6.51 g of itaconic acid, a hydrogen bond acceptor 13.52 g of betaine monohydrate and 98.5 μL of butyl 2-[(ethoxythiocarbonyl)thio]propionate were heated and stirred at 60° C. for 60 min to mix well to obtain a polymerizable deep eutectic solvent (PDES);
[0070] S2, irradiating the PDES under UV light (2 kW) for 300 s to obtain a dry ion conductor;
[0071] S3. 12.82 g of BA containing a double bond was mixed with 65.5 μL of ethyl 2-[(ethoxythiocarbonyl)thio]propionate, and then coated on the surface of the dry ion conductor. The mixture was irradiated with ultraviolet light for 300 to 400 s and cured to obtain a surface functionalized dry ion conductor. Example 10
[0072] A surface functionalized dry ion conductor, the preparation process is as follows:
[0073] S1. Mix 7.20 g of acrylic acid as a hydrogen bond donor, 3.55 g of acrylamide, 2.79 g of choline chloride as a hydrogen bond acceptor, and 98.5 μL of RAFT agent 2-[(ethoxythiocarbonyl)thio]butyl propionate under heating and stirring at 60° C. for 60 min to obtain a polymerizable deep eutectic solvent (PDES);
[0074] S2, irradiating the PDES under UV light (2 kW) for 300 s to obtain a dry ion conductor;
[0075] S3. 12.82 g of BA containing a double bond was mixed with 65.6 μL of ethyl 2-[(ethoxythiocarbonyl)thio]propionate, and then coated on the surface of the dry ion conductor. The mixture was irradiated with ultraviolet light for 300 to 400 s and cured to obtain a surface functionalized dry ion conductor. Embodiment 11
[0076] A surface functionalized dry ion conductor, the preparation process is as follows:
[0077] S1, heating and stirring 7.21 g acrylic acid as a hydrogen bond donor, 14.2 g acrylamide, 13.96 g choline chloride as a hydrogen bond acceptor and 98.5 μL RAFT agent 2-[(ethoxythiocarbonyl)thio]butyl propionate at 80° C. for 60 min to obtain PDES;
[0078] S2, irradiating the PDES under UV light (2 kW) for 400 s to obtain a dry ion conductor;
[0079] S3. 12.82 g of BA hydrophobic monomer containing a double bond is mixed with 87.5 μL of ethyl 2-[(ethoxythiocarbonyl)thio]propionate, and then coated on the surface of the dry ion conductor, irradiated with ultraviolet light for 300 to 400 s, and cured to obtain a surface functionalized dry ion conductor.
[0080] Performance Testing
[0081] The following performance tests were performed on the surface functionalized dry ion conductors described in Examples 1 to 11.
[0082] (1) Light transmittance
[0083] Test method: The light transmittance (transmittance) is recorded on an ultraviolet-visible (UV-vis) spectrometer. The transmittance of a sample strip with a thickness of 1 mm is measured, and the wavelength range of the transmitted light is 200 to 1000 nm. After testing, the transmittance of the surface functionalized dry ion conductors prepared in Examples 1 to 11 is greater than 90%, and they are all transparent elastomers. When placed on a paper with fonts printed on it, the fonts on the paper can be clearly seen. Figure 1 The figure shows a comparison of the surface functionalized dry ion conductor of Example 3 and the paper with printed characters, wherein Figure 1 (a) is the placement process diagram. Figure 1 (b) is the picture after the hand is removed.
[0084] (2) Hydrophobicity test
[0085] Test method: Use a surface contact angle meter to measure the contact angle of water on the surface of the dry ion conductor before and after functionalization. Drop a certain amount of deionized water droplets vertically on the surface of the dry ion conductor. The test found that the contact angles of the surface functionalized dry ion conductors of Examples 1 to 11 were significantly increased compared to the dry ion conductors before functionalization. Figure 4 is the contact angle of Example 3 when surface functionalization is not performed, Figure 5 This is the contact angle after surface functionalization (using hydrophobic monomer BA) in Example 3. Figure 6 is the contact angle after surface functionalization (using hydrophobic monomer TFPMA) in Example 7, Figure 7 This is the contact angle of Example 8 after surface functionalization (using hydrophobic monomer HA).
[0086] (3) Conductivity test
[0087] The electrochemical impedance spectroscopy method was used to measure the ionic conductivity of the 10×10×1mm 3 The dry ion conductor was sandwiched between two copper electrodes, and an AC impedance test was performed on an electrochemical workstation to calculate the conductivity. The test results show that the surface functionalized dry ion conductors of Examples 1 to 11 have little change in conductivity before and after functionalization. Figure 3 The conductivity comparison diagram of the dry ion conductors before and after surface functionalization of Examples 1 to 6 is shown, wherein Figure 3 (a) Electrical conductivity before surface functionalization, Figure 3 (b) is the conductivity after surface functionalization, compared with Figure 3 (a) and Figure 3 (b) It can be seen that the difference in conductivity of the surface functionalized dry ion conductor before and after functionalization is less than 28%, indicating that the conductivity of the dry ion conductor before and after surface functionalization is not much different and the conductivity is good.
[0088] (4) Mechanical properties test
[0089] The tensile test was carried out using a universal material tensile machine, and the chuck moving rate was 5 mm / min. The experiment found that the surface functionalized dry ion conductors of Examples 1 to 11 had a significantly improved stress and a small change in strain compared to the dry ion conductors before functionalization, indicating that the dry ion conductors after surface functionalization still have excellent mechanical properties, and the overall mechanical properties are improved. Figure 8 This is a diagram of the mechanical properties of the dry ion conductor before and after surface functionalization in Example 3.
[0090] (5) Ultraviolet absorption spectrum test
[0091] Use a UV-visible spectrophotometer to place the sample in a quartz tube for testing, with a scanning range of 1000 to 200 nm. Fig. 9The figure shows the UV absorption spectra of the dry ion conductor before and after surface functionalization of Example 3. The peak at 433 nm corresponds to the peak of the thiocarbonylthio terminal group of the RAFT agent, indicating that the thiocarbonylthio terminal group is still retained in the material before and after photocuring, thereby reinitiating polymerization and facilitating our post-functionalization treatment of the material.
[0092] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a surface functionalized dry ion conductor, characterized in that: The steps include: S1, stirring and mixing the hydrogen bond donor, hydrogen bond acceptor and RAFT agent at 50-80° C. to obtain a polymerizable low eutectic solvent; S2, irradiating the polymerizable low eutectic solvent under ultraviolet light to solidify it to obtain a dry ion conductor; S3, blending a hydrophobic monomer containing a double bond with a RAFT agent, coating the mixture on the surface of the dry ion conductor, irradiating the mixture with ultraviolet light, and curing the mixture to obtain a surface functionalized dry ion conductor; Wherein, in step S1, the hydrogen bond donor includes a soft monomer containing a C=C double bond and a hard monomer containing a C=C double bond; The hydrogen bond acceptor is a quaternary ammonium salt; The molar ratio of the soft monomer, the hard monomer and the hydrogen bond acceptor is 1:(0.5-2):(0.2-1).
2. The method for preparing a surface functionalized dry ion conductor according to claim 1, characterized in that: The soft monomer is acrylic acid or citraconic acid; and / or the hard monomer is acrylamide or itaconic acid; and / or the quaternary ammonium salt is choline chloride or betaine monohydrate.
3. The method for preparing a surface functionalized dry ion conductor according to claim 1, characterized in that: The hydrophobic monomer containing a double bond is one or more of butyl acrylate, 2,2,3,4,4,4-hexafluorobutyl acrylate, and 2,2,3,3-tetrafluoropropyl methacrylate.
4. The method for preparing a surface functionalized dry ion conductor according to claim 1, characterized in that: The RAFT agent is ethyl 2-[(ethoxythiocarbonyl)thio]propionate.
5. The method for preparing a surface functionalized dry ion conductor according to claim 1, characterized in that: In step S1, the molar ratio of the RAFT agent to the hydrogen bond donor is 1:(100-600).
6. The method for preparing a surface functionalized dry ion conductor according to claim 1, characterized in that: In step S3, the molar ratio of the RAFT agent to the hydrophobic monomer containing a double bond is 1:(100-600).
7. The method for preparing a surface functionalized dry ion conductor according to claim 1, characterized in that: In step S1, the hydrogen bond donor, hydrogen bond acceptor and RAFT agent are stirred at 60-80° C. for 30-60 min to be uniformly mixed.
8. The method for preparing a surface functionalized dry ion conductor according to claim 1, characterized in that: The ultraviolet light irradiation time in step S2 and step S3 is 300 to 400 seconds.
9. A surface functionalized dry ion conductor prepared by the method for preparing a surface functionalized dry ion conductor according to any one of claims 1 to 8, wherein the surface functionalized dry ion conductor is a dry ion conductor having a hydrophobic surface.
10. Application of the surface functionalized dry ion conductor according to claim 9 in the field of wearable electronics industry.